Genome Analysis and Therapeutic Evaluation of a Novel Lytic Bacteriophage of Salmonella Typhimurium: Suggestive of a New Genus in the Subfamily Vequintavirinae - Sadia Sattar; Inam Ullah; Sofia Khanum; Marc Bailie; Bushra Shamsi; Ibrar Ahmed; Tahir Abbas Shah; Sundus Javed; Aamir Ghafoor; Amna Pervaiz; Fakiha Sohail; Kaleem Imdad; et al. (Viruses, 2022)
Salmonella Typhimurium, a foodborne pathogen, is a major concern for food safety. Its MDR serovars of animal origin pose a serious threat to the human population. Phage therapy can be an alternative for the treatment of such MDR Salmonella serovars. In this study, we report on detailed genome analyses of a novel Salmonella phage (Salmonella-Phage-SSBI34) and evaluate its therapeutic potential. The phage was evaluated for latent time, burst size, host range, and bacterial growth reduction in liquid cultures. The phage stability was examined at various pH levels and temperatures. The genome analysis (141.095 Kb) indicated that its nucleotide sequence is novel, as it exhibited only 1–7% DNA coverage. The phage genome features 44% GC content, and 234 putative open reading frames were predicted. The genome was predicted to encode for 28 structural proteins and 40 enzymes related to nucleotide metabolism, DNA modification, and protein synthesis. Further, the genome features 11 tRNA genes for 10 different amino acids, indicating alternate codon usage, and hosts a unique hydrolase for bacterial lysis. This study provides new insights into the subfamily Vequintavirinae, of which SSBI34 may represent a new genus.